Pengaruh Mutasi dan Pemberian Insentif Terhadap Kinerja Pegawai Dinas Pekerjaan Umum dan Penataan Ruang - Arfandi Dinsar (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2021)
The purpose of this study was to determine the variable mutation and the provision of incentives partially and simultaneously affect the performance of the employees of the Public Works and Spatial Planning Office of Pinrang Regency. The approach in this study is associative with the type and source of data used is quantitative data. In this study, the population was the employees of the Public Works and Spatial Planning Department, totaling 73 people. then in this study used a sampling technique that is saturated sampling (census). This study uses data collection techniques of observation, questionnaires, documentation and studies). The data analysis technique used in this study used multiple linear regression. The results showed that partially Mutations (X1) and Incentives (X2) had a positive and significant effect on employee performance at the Public Works and Spatial Planning Office of Pinrang Regency. Simultaneously, Mutations and Incentives have a positive and significant effect on employee performance at the Public Works and Spatial Planning Office of Pinrang Regency.